Incidence of Bicompartmental Osteoarthritis in Patients Undergoing Total and Unicompartmental Knee Arthroplasty: Is the Time Ripe for a Less Radical Treatment? - Heekin, Richard David; Fokin, Alexander A. (The Journal of Knee Surgery, 2014)
We sought to determine the incidence of bicompartmental osteoarthritis among knee replacement patients for possible bone-sparing procedures. In 259 consecutive Knee Registry subjects undergoing total or unicondylar knee arthroplasty, all three compartments of the knee joint were evaluated. Radiographic images and preoperative cruciate ligaments assessment combined with intraoperative cartilage grading using Outerbridge classification was implemented for patients' evaluations. Among the candidates for knee replacement arthroplasty, 59% had osteoarthritis in all three compartments, 28% had bicompartmental disease, and 4% had unicompartmental disease. Nine percent of patients exhibited inconclusive osteoarthritis pattern. Only 5% of the patients were found to have cruciate ligaments impairment. Older patients ( > 65 years) were significantly more likely to have bi- and tricompartmental disease. We had found that 28% of our registry population had bicompartmental disease and infrequent impairment of cruciate ligaments, indicating that between one-fourth and one-third of patients undergoing total knee arthroplasty could be considered for bone preserving bicompartmental knee arthroplasty.
Keywords: bicompartmental osteoarthritis; bone-sparing arthroplasty